Implementasi Jaminan Produk Halal Melalui Sertifikasi Halal Pada Usaha Kecil Mikro di Kabupaten Sumenep - Dhimas, Putra; Makhtum, Ahmad (Politeknik Negeri Medan, 2022)
The concept of halal in the life of Indonesian people has been widely known. Halal in Islamic law is all good and clean food. The fundamental law of halal is that all sources of food from the sea, plants, and animals are considered halal except those that have been forbidden. The opposite of the concept of halal is forbidden, which means it is not justified os prohibited. Halal certification is the process to get a halal certificate in accordance with Islamic shari’a, aims to provide legal certainty of the halalnes of a product so that it can calm the mind for those who consume it. In law number 33 of 2014 concerning halal product guarantee article 4 states that halal certification is mandatory. The purpose of this study is to find out the extent of the implementation of halal product guarantees through halal certification on micro small business product in Sumenep Regency. The research method used is a descriptive qualitative approach research method, the data to be used are primary data and secondary data. From the research carried out, it can be seen that the implementation of halal certification has been carried out, this can be seen from the number of business actors who have registered their products even though there are still a small number of people who have not registered their products. The implementation of halal certification is certainly supported by several factors, in addition, there also several obstacles that hinder the implementation of halal certification. Konsep halal dalam kehidupan masyarakat Indonesia telah banyak dikenal. Halal dalam hukum Islam adalah semua makanan yang baik dan bersih. Hukum dasar halal adalah bahwa semua sumber makanan dari laut, tumbuhan dan binatang dianggap halal kecuali yang telah diharamkan. Lawan konsep halal adalah haram yang artinya tidak dibenarkan atau dilarang. Sertifikasi halal adalah proses untuk mendapatkan sertifikat halal sesuai dengan syari’at Islam, bertujuan untuk memberikan kepastian hukum kehalalan suatu produk sehingga dapat menentramkan batin bagi yang mengkonsumsinya. Dalam Undang-Undang No. 33 Tahun 2014 tentang Jaminan Produk Halal pada pasal 4 menyebutkan bahwa sertifikasi halal bersifat wajib. Penelitian ini bertujuan untuk mengetahui sejauh mana implementasi jaminan produk halal melalui sertifikasi halal pada produk usaha kecil mikro di Kabupaten Sumenep. Metode penelitian yang di gunakan ialah metode penelitian pendekatan kualitatif deskriptif. Data yang akan digunakan adalah data primer dan data sekunder. Dari penelitian yang dilaksanakan dapat diketahui bahwa impelementasi sertifikasi halal sudah terlaksana hal ini terlihat dari banyaknya pelaku usaha yang sudah mendaftarkan produknya meskipun masih ada sebagian kecil yang belum mendaftarkan produknya. Terlaksananya implementasi sertifikasi halal ini tentunya didukung oleh adanya beberapa faktor. Selain itu juga, terdapat beberapa kendala yang menghambat terlaksananya sertifikasi halal.